THE EFFECT OF THE INDIAN OCEAN DIPOLE (IOD) PHENOMENON ON OCEANOGRAPHIC PARAMETERS IN THE MALACCA STRAIT - Claudya, Sonia Glory; Siregar, Yusni Ikhwan; Mubarak, Mubarak (Asian Journal of Aquatic Sciences, 2023)
The Indian Ocean Dipole (IOD) phenomenon is a phenomenon that occurs in the Indian Ocean due to differences in sea surface temperature anomalies between the Western Indian Ocean and Eastern Indian Ocean regions. This interaction produces high pressure in the Eastern Indian Ocean (South of Java and West of Sumatra) which causes the flow of air masses to blow westward. The IOD phenomenon affects oceanographic parameters such as sea surface temperature, salinity, currents, and sea level rise in Indonesian waters. The Malacca Strait is a very important waterway because it connects the Indian Ocean and the South China Sea (Pacific Ocean) so it is strongly influenced by the IOD phenomenon. This research was conducted from November 2022 - February 2023. Global data collection in this study was located in the waters of the Strait of Melaka and data collection for validation was carried out in the waters of North Rupat. This study uses data analysis using secondary data and primary data to validate the secondary data used so that it can prove that the global data in this study are accurate. The results of this study found that in the period 2013 - 2022, the range of sea surface temperature of the Malacca Strait is 27 - 32°C. The salinity of the Malacca Strait waters ranges from 32.54 - 33.49 ppt. The current speed in the Malacca Strait is classified as weak to strong with the direction of movement of the Malacca Strait ocean currents back and forth. The Malacca Strait waters have a mixed tidal type of double daily inclination with an F value of 0.6 cm. The sea level rise in the Malacca Strait ranges from 0.50 - 0.76 cm. The IOD phenomenon affects sea surface temperature, salinity, sea level rise, and current velocity depending on the IOD phase.